Simulation of the explosion of a surface microprotrusion during a radio frequency breakdown - Oreshkin E. V.; Barengolts S. A.; Oreshkin V. I. Vladimir Ivanovich; Khishchenko K. V. (2019, 2019)
Заглавие с титульного экрана